(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: (1) Describing the employment status of Bachelor of Nutrition, (2) Describing job position suitability and the difficulties of Bachelor of Nutrition faced when working in field of clinical nutrition. Methods: A cross-sectional study, using an online survey conducted on 278 subjects of 6 Bachelor of Nutrition courses graduated in Hanoi Medical University. Results: The highest percentage of nutrition bachelors working at hospitals accounted for 37% and tends to decrease from course I to course VI. Professional suitability with job positions is highly appreciated in nutrition departments, nutrition clinics/consultants, and food processing companies. The difficulties that BN faced in field of clinical nutrition is not being able to participate in nutrition consultations, not being examined and assessed nutrition status for patients. Conclusion: The most of Bachelor of Nutrition are working on field of clinical nutrition, and on fields suitable for their profession. However, they have faced many limitations due to the lack of policies regulating functions and tasks on professional activities